The Effect of Perceived Organizational Support On Organizational Citizenship Behavior Through Organizational Commitment & Organizational Justice as Mediation Variables - Diaz Ayu Fardianasari; Arief Purwanto; Nasharuddin Mas (Journal of Management Research and Studies, 2025)
The purpose of this study wa to determine the effect of perceived organizational support on organizational citizenship behavior with organizational commitment as a mediating variable (Study at Btari Agency Malang City). The population in this study were all staf, both general and operational staff at Btari Agency Malang. The sampling technique in this study used "non probability sampling", and the sampling method in this study was "total sampling or census". Respondents in this study were 49 people through the Smart Partial Least Square (PLS) Software. The results of this study indicate that; (1) perceived organizatinal support has a positive and significant effect on organizational citizenship behavior. (2) perceived organizatinal support has a positive and significant effect on organizational commitment. (3) organizational commitment has a positive and significant effect on organizational citizenship behavior. (4) perceived organizatinal support and organizational commitment to organizational citizenship behavior, shows the results of organizational commitment can partially mediate the relationship of perceived organizatinal support to organizational citizenship behavior.